Formulation of cambete biscuits high in energy and protein as a snack for children with tuberculosis (TB) - Iskari Ngadiarti; Muntikah Muntikah; Bintang Rizkia Putri; Aurasyifa Salsabila Nixon; Sherlita Jasmine Khaerunissa (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Tuberculosis (TB), particularly in children, often leads to undernutrition owing to increased metabolic demands and reduced food intake. This study aimed to evaluate the organoleptic characteristics, acceptability, and nutritional quality of cambete biscuits made from a mixture of eel and tempe flours at different concentrations. This study used a completely randomized design (CRD) with three treatment factors and three replications (2,5%, 3,7%, and 5% substitutions of eel and tempe flour), which took place in Jakarta Health Polytechnic II from April to June 2024. The biscuits were assessed using sensory (organoleptic) and hedonic tests by moderately trained panelists. Proximate analysis was performed to determine nutrient content. Data were analyzed using the Friedman test. The results showed no significant differences in color (P =0,101), aroma (P =0,410), taste (P =0,306), or texture (P =0,598) among the different flour formulations. One serving (46 g, 2 biscuits) of Cambete biscuits provides 212,14 kcal of energy, 3,88 g of protein, and is favored by 63,4% of panelists. In conclusion, this product has potential as a complementary food for children with TB owing to its high energy content and the use of locally available ingredients.